PENGARUH CARA BELAJAR TERHADAP HASIL BELAJAR SISWA MATEMATIKA SMK JANUR PERSADA SIGI - Dewi Sri Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This study aims to determine whether or not there is an influence of student learning styles on learning outcomes of mathematics. In addition, this study aims to determine how much influence students learning styles about the learning outcomes of mathematics in SMK JANUR PERSADA SIGI. This type of research is Expost Facto's research. The population in this study were all students of the SMK JANUR PERSADA SIGI, the number of students is 80 students consisting, students of class X as many as 25 students, class XI as many as 20 students and class XII as many as 35 students. The sample in this study was all students in the SMK JANUR PERSADA SIGI. The research instruments used were questionnaires on learning styles and Mathematics Learning Outcomes Test. Analysis of the results of the research data was carried out using the SPSS version 20.0 computer program. The results of the study show that: (1) Most students of the SMK JANUR PERSADA SIGI have learning styles in the moderate category with an average score of 38.50 with a standard deviation of 5.4321 from a minimum score of 14 to maximum 56; and mathematics learning outcomes in the very low category with an average score of 29.31 with a standard deviation of 7.833 from a minimum score of 0 to maximum 100. (2) The learning styles the SMK JANUR PERSADA SIGI is in the moderate category. (3) The mathematics learning outcomes of the SMK JANUR PERSADA SIGI are in the very low category. (4) the influence of The way to study with mathematics learning outcomes is 51.1%. While 48.9% of student learning outcomes are influenced by other variables not examined